Split CV mobility at low temperature operation of Ge pFinFETs fabricated with STI first and last processes. (13th October 2016) - Oliveira, A V; Simoen, E; Agopian, P G D; Martino, J A; Mitard, J; Witters, L; Langer, R; Collaert, N; Thean, A; Claeys, C
Abstract: The effective hole mobility of long strained Ge pFinFETs, fabricated with shallow trench isolation (STI) first and last approaches, is systematically evaluated from room temperature down to 77 K, from planar-like (100 nm) to narrow (20 nm) devices. The goal is to identify the dominant scattering mechanism. Here, the split capacitance-voltage (CV) technique has been applied, based on combined current–voltage ( I–V ) and CV measurements. It is shown that even at 77 K, the phonon scattering mechanism dominates the STI last process, while the Coulomb scattering strongly affects the STI first approach. On the other hand, the latter shows slightly higher hole mobility compared to the STI last counterpart.